2000
DOI: 10.1034/j.1399-3003.2000.16f23.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator associated pneumonia: quality of nonbronchoscopic bronchoalveolar lavage sample affects diagnostic yield

Abstract: The importance of predefined criteria for acceptable samples of respiratory therapists′ obtained lower respiratory samples were studied, using a nonbronchoscopic bronchoalveolar lavage (BAL) protocol for ventilated patients in the intensive care unit. Therapists were instructed and asked to follow guidelines for obtaining samples. Over one year, 219 samples were obtained by respiratory therapists. Of these, 115 were considered to be adequate samples using the following criteria: 60 mL of instilled volume, at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…However, in the present study of dogs with pulmonary disease, only 5 of the 22 low‐retrieval BALF samples had inadequate cell numbers for analysis and half (11/22) still yielded a definitive or supportive cytologic diagnosis. This finding agrees with a report in humans that BALF retrieval of at least 10% of the original aliquot still can reflect alveolar sampling . In general, maximal infusate retrieval should be attempted for any BAL to maximize the likelihood of retrieving alveolar cells.…”
Section: Discussionsupporting
confidence: 90%
“…However, in the present study of dogs with pulmonary disease, only 5 of the 22 low‐retrieval BALF samples had inadequate cell numbers for analysis and half (11/22) still yielded a definitive or supportive cytologic diagnosis. This finding agrees with a report in humans that BALF retrieval of at least 10% of the original aliquot still can reflect alveolar sampling . In general, maximal infusate retrieval should be attempted for any BAL to maximize the likelihood of retrieving alveolar cells.…”
Section: Discussionsupporting
confidence: 90%
“…The minimum amount of BAL fluid necessary to perform the typical battery of laboratory tests varies by institution. For adults it is recommended that the minimal total volume retrieved is >30% of the instilled volume (48).…”
Section: The Role Of the Rigid Bronchoscopementioning
confidence: 99%
“…In one study of nonbronchoscopic lavage, it was shown that patients with a greater than 5% return of instilled fluid have a higher diagnostic yield. 41 For safety reasons, some feel that the lavage should be stopped if the volume instilled becomes more than 100 mL larger than the aspirated volume. Because this will depend on the volume of the instilled aliquots, the bronchoscopist should be aware of the aspirated volume after each aliquot is instilled.…”
Section: Variability Of Lavage Returnmentioning
confidence: 99%